Analisis Kebutuhan Buku Ajar Bahasa Inggris dalam Materi Pembelajaran Tingkat SMK Jurusan Teknik Komputer Jaringan - Sutarji Sutarji (Jurnal Pendidikan Indonesia, 2022)
The systematization of books (teaching materials) so that students can use them to achieve learning objectives. Teachers must have the ability to develop teaching materials according to the needs of students. Lack of textbooks in teaching at the SMK level, especially English textbooks. The purpose of this study was to identify some data and the match between the content in English textbooks and the needs of students at SMK 1 Gondang, Nganjuk. This study uses a qualitative method with a descriptive approach. Collecting data through interviews and questionnaire surveys on students and literature review. The population and sample in this study were grade X students and English textbooks for SMK. It can be seen that the needs of SMK students majoring in Network Computer Engineering related to learning English are in accordance with the existing KD SK in accordance with the knowledge learned in Network Computer Engineering. Based on the results of interviews, it was stated that the needs of SMK students majoring in TKJ in English are those who introduce the industrial world a lot, the ability to communicate in the general and industrial environment, and are familiar with vocabulary, especially terms, procedures, and the competence of SMK majoring in Network Computer Engineering in general. The description above shows that students' expectations and learning situations can build English language learning in meeting the needs of students effectively. The needs of SMK students majoring in TKJ for those related to learning English are in accordance with the existing KD SK and in accordance with the knowledge learned in TKJ.